Health care provider and client experiences of counselling on depot medroxyprogesterone acetate subcutaneous (DMPA-SC) for self-injection in Malawi. - Chelsey Porter Erlank; Gracious Ali; Frehiwot Birhanu; Melinda Stanley; Jessie Salamba Chirwa; Fannie Kachale; Andrews Gunda (Public Library of Science (PLoS), 2023)
Since the introduction of subcutaneous depot medroxyprogesterone acetate (DMPA-SC) in 2018, Malawi has achieved national coverage of trained providers in the public sector and steady increases in uptake of DMPA-SC. However, the rate of clients opting to self-inject DMPA-SC has remained lower than early acceptability studies suggested. Providers play an instrumental role in building client confidence to self-inject through counselling/training. This cross-sectional qualitative study explored the perspectives of providers and injectable clients on the integration of self-injection into contraceptive counselling, to identify best practices and potential gaps. The study was conducted at public sector sites in three districts (Nkhotakota, Mzimba South, Zomba) in Malawi. In-depth interviews were conducted with provider-administered injectable clients, self-injecting clients, and DMPA-SC trained providers. All providers interviewed reported successfully integrating self-injection into their approach. During group health education sessions, some providers reported focusing on benefits of self-injection to spark interest in the method, and then follow that up with more in-depth information during individual counselling. Due to time pressures, a minority of providers reported replacing individual counselling with small-group counselling and limited use of elements such as visualizations and demonstrations. Most providers skipped client practice on inanimate objects, feeling this was either not necessary or inappropriate given stock constraints. Self-injection clients tended to credit their decision to take up SI to receiving lengthy, comprehensive counselling/training, often inclusive of reassuring messages, visualizations, demonstrations and sometimes repeated trainings over time. Provider-administered clients tended to credit their lack of uptake of self-injection to fear and lack of confidence, often blaming themselves instead of the quality of their counselling/training-even while many felt their counselling/training had been rushed or incomplete. Providers should be supported to overcome time- and resource-pressures to invest in counselling/training best practices, to ensure sufficient support is provided to clients interested in self-injection.